350 A Comparison of Incidental and Symptomatic Unruptured Brain Arteriovenous Malformations in Children. (April 2023) - Lu, Alex Y.; Winkler, Ethan A.; Garcia, Joseph; Raygor, Kunal P.; Fullerton, Heather; Fox, Christine; Kim, Helen; Auguste, Kurtis Ian; Sun, Peter P.; Hetts, Steven; Lawton, Michael T.; Abla, Adib Adnan; et al.
Abstract : INTRODUCTION: Unruptured brain arteriovenous malformations (AVMs) may present with headaches, seizures, and/or neurologic deficits. A smaller number of cases may be discovered incidentally. These lesions remain incompletely understood due to their sparse reporting. METHODS: We performed a retrospective analysis of patients presenting with brain AVMs from 1998 to 2021 at the University of California, San Francisco. Inclusion criteria included age ≤18 at time of presentation with angiographically-proven unruptured AVM diagnosed postnatally. RESULTS: Of 76 children with unruptured AVMs, 66 (86.8%) presented with headaches, seizures, and/or neurologic deficit. Ten (13.1%) were incidentally discovered through unrelated disease workup (50%), cranial trauma (40%), or research study participation (10%). Compared to symptomatic unruptured AVMs, incidental unruptured AVMs possessed smaller mean nidus maximum diameter (2.82 ± 1.1 vs. 3.98 ± 1.52 cm, p = 0.025) and deep venous drainage proportion (20% vs. 61%, p = 0.036). They also presented at earlier ages (10 ± 5.2 vs. 13.5 ± 4 years, p = 0.043) with longer durations to first treatment (541 ± 922 vs. 196 ± 448 days, p = 0.005). During the period of observation, one patient developed recurring headaches and demonstrated AVM nidus growth. Four AVMs greater than 3 centimeters or in deep location were treated with radiosurgery. Six other AVMs were treated with surgical resection with 2 receiving preoperative embolization. Seven AVMs (70%) were obliterated on last follow-up. Postprocedural complications included 2 transient neurologic deficits following resection and 1 delayed seizure development following radiosurgery. The mean follow-up period was 5.1 ± 5.8 years without any hemorrhage episodes. CONCLUSIONS: A substantial proportion of pediatric patients with unruptured AVMs are discovered incidentally. With earlier presentation and more elementary angioarchitecture than symptomatic unruptured AVMs, these incidental lesions provide a snapshot into AVM natural history before symptom development or rupture.